(untitled) (Swiss Medical Weekly, 2025)
AIM: To establish local diagnostic reference levels for cardiac implantable electronic device procedures and to compare local practice with national guidelines. METHODS: A retrospective cohort study including all consecutive patients from October 2018 to October 2020 who underwent implantation of a cardiac implantable electronic device including pacemaker, implantable cardioverter defibrillator (ICD), cardiac resynchronisation therapy (CRT) or lead extraction / device explantation. Data was collected from a dose management system and cross-checked for accuracy with the patient information system. The pre-specified outcome was patient radiation exposure, evaluated with the kerma area product (KAP), cumulative dose, fluoroscopy time and number of cine acquisitions. The median values were set as local diagnostic reference levels. RESULTS: A total of 541 patients were included. 28.3% had a conventional pacemaker, 22.0% a leadless pacemaker, 21.1% an ICD and 17.2% a CRT implanted, while lead extraction / device explantation was performed in 11.5% of patients. The local diagnostic reference levels for the kerma area product were lower than the national Swiss diagnostic reference levels (0.4 Gray [Gy]∙cm2 vs 30 Gy∙cm2 for conventional pacemakers; 0.4 Gy∙cm2 vs 20 Gy∙cm2 for ICDs; 10.2 Gy∙cm2 vs 57 Gy cm2 for CRTs). Similarly, the local diagnostic reference levels for cumulative dose and fluoroscopy time were below national diagnostic reference levels. CONCLUSIONS: Local diagnostic reference levels values were far below national diagnostic reference levels. A multicentre approach to assess patient radiation exposure in current practice is strongly desired to establish revised national diagnostic reference levels.